Realistic Mathematics Education (RME) pada Efikasi Diri Siswa - Meti Rusmiati (Cahaya Ilmu Cendekia Publisher, 2022)
Research objectives: This study aims to determine the difference in self-efficacy of students who are treated with Realistic Mathematics Education (RME) approaches and direct learning models. Methodology: This type of research is a quantitative descriptive study with a pretest-posttest control group design. The sample in this study was class VIII A with the treatment of Realistic Mathematics Education (RME) approach and class VIII B with a direct learning model to see its effect on self-efficacy. The instruments in this study were self-efficacy questionnaires and observation sheets. Data analysis was carried out using two-party t-test. Main findings: The results showed that there were differences in self-efficacy between students who were treated with the Realistic Mathematics Education (RME) approach and students who were treated with the direct learning model. So it can be concluded that the Realistic Mathematics Education (RME) approach has a significant influence on students' self-efficacy on function material. The Novelty of research: With this research, it can be used as an alternative in learning mathematics and is able to influence students' self-efficacy in mathematics.